MERACIK PEMBELAJARAN KOLABORATIF BERBANTUAN PADLET UNTUK MENULIS TEKS EKSPLANASI - Astuti, Yuli; Abidin, Yunus; Cahyani, Isah (UNIB Press, 2022)
This study aims to create a meaningful learning design in learning to write explanations with padlet. This research was carried out using the 4D research and development method. The research subjects were students of Madrasah Aliyah Bandung Regency. Data were collected using instruments in the form of interviews, assessments, and questionnaires. The research data were processed both quantitatively and qualitatively. The results showed that the design of developing a meaningful learning model assisted by the padlet application in learning to write explanatory texts described a harmonious combination between the collaborative learning syntax and the padlet application; the application of the development of meaningful learning models assisted by padlet applications can improve students' writing skills in writing explanatory texts, and the response of the participants to meaningful learning models assisted by padlet applications in learning to write explanatory texts is very good.